2023
DOI: 10.1177/1759720x231197094
|View full text |Cite
|
Sign up to set email alerts
|

Anti-sclerostin antibodies: a new frontier in fragility fractures treatment

Giovanni Iolascon,
Sara Liguori,
Marco Paoletta
et al.

Abstract: Bone fragility is the determinant of the increased risk of minimal trauma fracture and must be treated with a multimodal approach that includes pharmacological therapy, physical exercise, and adequate nutrition. Pharmacological therapy, to date based on the administration of antiresorptive drugs, such as bisphosphonates and denosumab, or osteoanabolic drugs, such as teriparatide and abaloparatide, has shown to be effective in reducing the risk of fracture in osteoporotic patients. In the context of the cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…27,28 Several studies investigated the prevalence of osteoporosis in PD, typically including patients with worse Hoehn & Yahr scores compared to the current population. [22][23][24][25][26][27][28][29] A previous study found a high prevalence of bone loss in patients with PD at the early stages based on quantitative parameters (i.e. BMD); reporting osteopenia and osteoporosis in 41.4% and 11.8% of patients, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…27,28 Several studies investigated the prevalence of osteoporosis in PD, typically including patients with worse Hoehn & Yahr scores compared to the current population. [22][23][24][25][26][27][28][29] A previous study found a high prevalence of bone loss in patients with PD at the early stages based on quantitative parameters (i.e. BMD); reporting osteopenia and osteoporosis in 41.4% and 11.8% of patients, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…24 Regarding other therapeutic strategies, including denosumab, a monoclonal antibody that inhibits osteoclast maturation by binding to receptor activator of nuclear factor j B ligand (RANKL), anabolic agents such as parathyroid hormonerelated protein analogues (teriparatide and abaloparatide) and dual-action drugs such as romosozumab, a monoclonal antibody sclerostin inhibitor, these have demonstrated efficacy in improving bone density and in reducing risk of fragility fractures in people affected by osteoporosis. 25,26 However, it should be noted that denosumab and romosozumab seem to reduce the risk of falls by 20% in the general population, but otherwise only limited evidence is available about the effectiveness of these drugs in PD patients. 27,28 Several studies investigated the prevalence of osteoporosis in PD, typically including patients with worse Hoehn & Yahr scores compared to the current population.…”
Section: Discussionmentioning
confidence: 99%
“…The most well-known sclerostin inhibitor, approved by the FDA and approved in clinical trials, is romosozumab. This preparation increases the number of osteoblasts, improves mechanical strength by increasing bone mass, improves structural and architectural characteristics, and optimizes the composition of bone tissue [163,164]. However, romosozumab has a limited period of effectiveness, which requires concomitant antiresorptive therapy [164].…”
Section: Antisclerostin Antibodiesmentioning
confidence: 99%
“…Sclerostin, derived from osteocytes, navigates through canalicular networks to reach bone surfaces. Upon reaching these surfaces, sclerostin impedes the canonical Wnt-beta-catenin pathway, thereby reducing osteoblastogenesis and accelerating osteoclastogenesis [ 1 3 ]. In 2019, the European Medicines Agency approved romosozumab, an anti-sclerostin antibody, for osteoporosis treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the key mechanisms by which glucocorticoids diminish the production of osteoblasts is through the antagonism of the Wnt/β-catenin signaling pathway [ 8 ]. Additionally, sclerostin acts as a Wnt signaling inhibitor, obstructing osteogenic differentiation and impeding the acquisition of bone mass [ 3 , 8 , 9 ]. Fascinatingly, treatments with sclerostin-neutralizing antibodies demonstrated the ability to reduce overall marrow adiposity in both a time-dependent and dose-dependent fashion [ 5 ].…”
Section: Introductionmentioning
confidence: 99%